Rigidez de planos projetivos minimizantes de área em 3-Variedades - Campos, Geovan Carlos Mendonça (2016)
In this work, we talk about the article "Area-Minimizing Projective Planes in 3- Manifolds" due to Hubert Bray, Simon Brendle, Michael Eichmair and Andr´e Neves. In this article they consider a compact Riemannian 3-manifold (M; g) with positive scalar curvature and an embedded projective plane. In these conditions they prove a higher estimate of curvature, in term of infimum of the scalar curvature of (M; g), for the area of the projective plane that has the smallest area within the class of all surfaces Σ ⊂ M homeomorphic to projective plane. Furthermore, they prove that this inequality is great. More precisely, they get that if this equality hold in (M 3; g), so M is isometric to the three-dimensional projective space RP3 with constant sectional curvature.